2017
DOI: 10.11604/pamj.2017.28.282.14361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity, diabetes mellitus, hypertension and associated risk factors in a mining workforce, Democratic Republic of Congo

Abstract: IntroductionThe burden of non-communicable diseases (NCDs) is increasing in low and middle-income countries (LMIC). According to the World Health Organization (WHO) the largest increase occurs in Africa. Obesity, diabetes mellitus and hypertension (ODH) are major risk factors for cardiovascular diseases, causing nearly 18 million deaths worldwide. Various risks associated with mining as an occupational activity are implicated in NCDs' occurrence. This study describes the baseline prevalence of ODH and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 30 publications
3
33
2
4
Order By: Relevance
“…The objective of this study was to measure trends in ODH prevalence over time and to identify important risk factors contributing to changes in prevalence in the study population. This study [14]. Like another study on office workers in Kinshasa [19], the present study showed that mine workforce is also a high-risk occupational group for NCDs associated with high prevalence of ODH risk factors.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The objective of this study was to measure trends in ODH prevalence over time and to identify important risk factors contributing to changes in prevalence in the study population. This study [14]. Like another study on office workers in Kinshasa [19], the present study showed that mine workforce is also a high-risk occupational group for NCDs associated with high prevalence of ODH risk factors.…”
Section: Discussionsupporting
confidence: 75%
“…Like another study on office workers in Kinshasa [19], the present study showed that mine workforce is also a high-risk occupational group for NCDs associated with high prevalence of ODH risk factors. Without intervention, the percentage of pre-obese (19.7%), prediabetic (16.5%), and pre-hypertensive (47.8%) individuals identified in the 2010 baseline study are predicted to transition to full ODH status eventually, thus increasing the burden of NCDs on workforce productivity and society as a whole [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Also in the study done by Mawaw et al on 2749 mine workers shows the prevalence of hypertension and diabetes as 18.2% and 11.7% respectively. 16 Prevalence of chronic respiratory symptoms in Bhelkar et al is lower than our study which is 21.56%. 13 Prevalence of peptic ulcer in coal mine workers in our study shows 2.84% and which are seen only in an underground coal mine workers may be due to stress and irregular food habits which is lower than a study conducted by Zahorski et al among 9361 coal mine workers shows the prevalence of peptic ulcer disease as 7.92%.…”
Section: Discussioncontrasting
confidence: 73%